Developing training for teachers of children with special needs in Barbados : challenges and opportunities - Hornby, Garry (1997)
Discusses various factors which present particular challenges to the organisation of effective special needs training. Notes several positive forces supporting constructuive changes in special education provision and training in Barbados and outlines the essential components of effective special needs provision. Presents a comprehensive model for providing the training necessary to equip special education personnel to implement these components.